An improved filtering method for digital elevation models construction based on LiDAR - Yongquan Li; Xiangxi Dai; Mingxiao Wang; Zhizhou Huang (2010 18th International Conference on Geoinformatics, 2010)
LiDAR (Light Detection and Ranging) is a positive remote sensing technology. In this paper, with analyzed the characteristic of LiDAR data and discussed the advantages of LiDAR data, we present an improved data filtering algorithm for LiDAR data. It is basing on the last return laser pulses and tries to design an fast pre-processing LiDAR point data with the purpose of DEM Modeling from LiDAR based point cloud data. The algorithm contains two times of filtering with different aims and data process strategies. Experiments of real terrain area are presented for testing efficiency and accuracy of this filtering method.